(untitled) (Research, Society and Development, 2022)
This study intends to discuss the paths that the school must follow so that it can, in fact, contribute to the development of people, considering the knowledge of human rights in the expansion of education and social awareness. The historical process of human rights and its dissemination to society are recorded to support the theoretical foundation proposed in this research. The importance of the school, the pedagogical practices adopted by the teachers for the education of the social individual, to the detriment of the essential rights, is raised. Authors such as Freire, Silva, Vieira, Magendzo and Benevides support this analysis theoretically. In fact, it is clear the relevance of working with the Human Rights theme in schools, and how important is the role of education in the awareness of human dignity, because besides training for citizenship and for work, the social function of the school is to prepare students for living in a culture of diversity, rights, and socio-cultural duties.